Predicted CD4+ T cell infiltration levels could indicate better overall survival in sarcoma patients. Issue 1 (January 2021) - Bi, Qing; Liu, Yang; Yuan, Tao; Wang, Huizhen; Li, Bin; Jiang, Ye; Mo, Xingkui; Lei, Yonghong; Xiao, Yanbin; Dong, Suwei; Shen, Hongmei; Lv, Li; et al.
Objective: The role of tumor-infiltrating lymphocytes (TILs) has not yet been characterized in sarcomas. The aim of this bioinformatics study was to explore the effect of TILs on sarcoma survival and genome alterations. Methods: Whole-exome sequencing, transcriptome sequencing, and survival data of sarcoma were obtained from The Cancer Genome Atlas. Immune infiltration scores were calculated using the Tumor Immune Estimation Resource. Potential associations between abundance of infiltrating TILs and survival or genome alterations were examined. Results: Levels of CD4 + T cell infiltration were associated with overall survival of patients with pan-sarcomas, and higher CD4 + T cell infiltration levels were associated with better survival. Somatic copy number alterations, rather than mutations, were found to correlate with CD4 + T cell infiltration levels. Conclusions: This data mining study indicated that CD4 + T cell infiltration levels predicted from RNA sequencing could predict sarcoma prognosis, and higher levels of CD4 + T cells infiltration indicated a better chance of survival.